CITIES AND MIGRATION – BIBLIOMETRIC EVIDENCE FROM A SPATIALLY BIASED FIELD OF KNOWLEDGE PRODUCTION. Issue 2 (15th March 2022) - Schmiz, Antonie; Felgentreff, Carsten; Franz, Martin; Paul, Marcel; Pott, Andreas; Räuchle, Charlotte; Schrader, Sebastian
ABSTRACT: Research output on the nexus of cities and migration has grown considerably since the local turn in migration policy. Knowing that this interdisciplinary research field has always shown a preoccupation with certain locations and has long been dominated by particular research topics, we wonder whether recent knowledge production is still characterized by a spatial one-sidedness that produces topical imbalances. Pursuing a reflexive perspective in the overlapping field of urban studies and migration studies, we chose to scrutinize the places of research: Where are the places of knowledge production, and which places are referred to and examined empirically? To find sound answers, we have examined more than 500 exemplary articles published over a period of ten years in ten prominent journals of migration studies or urban studies. With the help of bibliometric analysis, we can reveal particular patterns in the researched sites and researchers' academic affiliations. Our study detects a clear dominance of research about the Global North, the places of migrant arrival, and larger cities. The results indicate both similarities and differences between city-related migration studies and migration-related urban studies. Thus, this study uncovers blind spots and illustrates how and why current—but nevertheless historically rooted—research practices portray migration movements and cities in a biased way.